2013
DOI: 10.1017/s031716710001489x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of BoNT A in Parkinson's Disease Upper Limb Tremor Management

Abstract: Abstract:Objective:One the greatest challenges of BoNT A therapy for tremor lies in the complexity and variation of components involved in tremor movement, and the lack of objective measures to determine these components. This 3 month open-label single injection study aims to couple clinician best judgment with kinematics to improve effect of BoNT A (incobotulinumtoxinA) injection in 7 patients with upper limb Parkinson's disease (PD) tremor.Methods:Injection was guided with clinical and kinematic assessment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 26 publications
0
35
0
2
Order By: Relevance
“…This demonstrated the low agreement between clinical and objective assessments and highlighted the inherent difference between these assessment techniques. Samotus and colleagues and Rahimi and colleagues reported effect of BoNT-A for ET and PD tremor, respectively, following a 38-week treatment period and strongly suggested that the use of kinematic tremor analysis could continue to better tailor BoNT-A parameters to changes in each individual’s tremor [1416]. By using kinematic data instead of visual assessment, physicians that are expert injectors but not experienced tremor assessors have a better chance in treating this disorder with ease using this systematic approach.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This demonstrated the low agreement between clinical and objective assessments and highlighted the inherent difference between these assessment techniques. Samotus and colleagues and Rahimi and colleagues reported effect of BoNT-A for ET and PD tremor, respectively, following a 38-week treatment period and strongly suggested that the use of kinematic tremor analysis could continue to better tailor BoNT-A parameters to changes in each individual’s tremor [1416]. By using kinematic data instead of visual assessment, physicians that are expert injectors but not experienced tremor assessors have a better chance in treating this disorder with ease using this systematic approach.…”
Section: Discussionmentioning
confidence: 99%
“…Tremor features were extracted from the angular signal data using custom-written software in MatLab ® (Version 2011a) [1416]. For each participant, mean total tremor amplitude at each joint was displayed as angular root mean squared (RMS) amplitude degrees for each scripted task over three trials.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…No new controlled trials have specifically addressed PD tremor, but some open‐label observations provide interesting data for potential approaches. A 3‐month single‐injection study in seven patients suggested that botulinum toxin is effective for the management of upper limb PD‐related tremor, and another open‐label observational study in 22 patients with PD found a significant improvement of tremor 30 minutes after smoking cannabis …”
Section: Treating Tremormentioning
confidence: 99%